A dog's tooth - Rowe, William Woodin; Banigan, Christopher (Ithaca, N.Y. : Snow Lion Publications, 1998)
A retelling of the Tibetan tale of deception and faith in which a young man who fails to obtain a sacred relic for his dying mother gives her a dog's tooth instead.
Keywords: Tales -- China -- Tibet Autonomous Region; Folklore -- China -- Tibet Autonomous Region